Photosynthetic induction and activity of enzymes related to carbon metabolism: insights into the varying net photosynthesis rates of coffee sun and shade leaves - Martins, Samuel Cordeiro Vitor; Detmann, Kelly Coutinho; Reis, Josimar Vieira dos; Pereira, Lucas Felisberto; Sanglard, Lílian Maria Vincis Pereira; Rogalski, Marcelo; DaMatta, Fábio Murilo (Theoretical and Experimental Plant Physiology, 2013)
The shade leaves of coffee (Coffea arabica L.) apparently retain a robust photosynthetic machinery that is comparable to that of sun leaves and can fix CO2 at high rates when subjected to high light intensities. This raises the question of why the coffee plant would construct such a robust photosynthetic machinery despite the low photosynthetic rates achieved by the shade leaves at low light supply. Here, we grew coffee plants at 100% or 10% full sunlight and demonstrated that the shade leaves exhibited faster photosynthetic induction compared with their sun counterparts, in parallel with lower loss of induction states under dim light, and were well protected against short-term sudden increases in light supply (mimicking sunflecks). These findings were linked to similar photosynthetic capacities on a per mass basis (assessed under nonlimiting light), as well as similar extractable activities of some enzymes of the Calvin cycle, including Rubisco, when comparing the shade and sun leaves. On the one hand, these responses might represent an overinvestment of resources given the low photosynthetic rates of the shade leaves when light is limiting; on the other hand, such responses might be associated with a conservative behavior linked to the origin of the species as a shade-dwelling plant, allowing it to maximize the use of the energy from sunflecks and thus ultimately contributing to a positive carbon balance under conditions of intense shading.
Keywords: Coffea; Photosynthesis; Photosynthetic induction kinetics; Sun/shade tolerance; Sunflecks